2009
DOI: 10.1159/000208519
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing in Colonic Anastomosis in Hypothyroidism

Abstract: Colonic anastomosis healing in hypothyroidism was evaluated. Twenty Wistar rats were separated into two groups: the study group (n = 10), which underwent total thyroidectomy to induce hypothyroidism, and the control group (n = 10). After 10 weeks, hypothyroid status was confirmed by blood tests (p < 0.0001). Three days later, a colonic anastomosis was performed, and the animals were sacrificed 1 week later. The colon containing the anastomosis was resected for bursting strength tests and histological studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 96 publications
0
4
0
2
Order By: Relevance
“…In animal models, decreased collagen bursting strength and decreased collagen density has been observed in hypothyroid rats in colonic anastomosis 40 , and decreased collagen deposition in tracheal sutures. 44 In addition to its role in wound healing, thyroid hormone is one of the critical systemic factors for fracture repair and hypothyroidism has been shown to inhibit endochondral ossification, resulting in an impaired fracture-repair process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In animal models, decreased collagen bursting strength and decreased collagen density has been observed in hypothyroid rats in colonic anastomosis 40 , and decreased collagen deposition in tracheal sutures. 44 In addition to its role in wound healing, thyroid hormone is one of the critical systemic factors for fracture repair and hypothyroidism has been shown to inhibit endochondral ossification, resulting in an impaired fracture-repair process.…”
Section: Discussionmentioning
confidence: 98%
“…31 Previous studies have shown that the composition of collagen may be altered in hypothyroidism, with a prevalence of immature, type III collagen seen compared to type I collagen in experimental animal models of hypothyroidism. 40 The quality of the collagen itself may also be altered in hypothyroidism, and shorter and thinner collagen fibers have been observed in pig models. 7…”
Section: Discussionmentioning
confidence: 99%
“…Although the main action of thyroid hormones in skin is not well identified, several lines of evidence indicate an important role for thyroid hormones in promotion of wound healing. First, hypothyroidism is associated with retarded wound repair probably through decreasing collagen synthesis and or keratinocyte proliferation [21,23,24] which is reversible with thyroid hormone replacement [21,25]. Second, in vitro and in vivo studies have designated that thyroid hormones stimulate keratinocyte and epidermal proliferation as well as hair growth [20,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…5 While wound healing depends on connective tissue activity and cellular proliferation, synthesis of connective tissue in the skin, such as collagen, and tissue tensile strength decrease in those with hypothyroidism. 6 T3 in culture medium can induce fibroblast and keratinocyte proliferation. 5 Wound healing is a complicated process that involves clot formation, inflammation, granulation, epithelialization, and remodeling.…”
Section: Introductionmentioning
confidence: 99%